Muslim networks and transnational communities in and across Europe - Allievi, Stefano; Nielsen, Jørgen S. (Leiden ; Boston : Brill, 2003)
The topic of this collection of articles is the increasingly transnational nature of Islam in Europe as well as the mechanisms by which the transnationalism is activated, especially the media. The papers integrate specific case studies with more general and thematic considerations.
Preface; List of Contributors; CHAPTER ONE: Islam in the public space: social networks, media and neo-communities; CHAPTER TWO: Transnational Islam and the integration of Islam in Europe; CHAPTER THREE: Gender, generation, and the reform of tradition: from Muslim majority societies to Western Europe; CHAPTER FOUR: 'Human nationalisms' versus 'inhuman globalisms': cultural economies of globalisation and the re-imagining of Muslim identities in Europe and the Middle East.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Muslims -- Europe; Europe -- Ethnic relations; Islam in mass media; Minorities -- Europe; Muslims -- Cultural assimilation -- Europe; Musulmans -- Europe; Islam dans les médias.; Minorités -- Europe; Musulmans -- Acculturation -- Europe; Europe -- Relations interethniques; SOCIAL SCIENCE -- Discrimination & Race Relations; Ethnic relations; Islam in mass media; Minorities; Muslims; Muslims -- Cultural assimilation; Europe; Globalisierung; Islam; Kommunikationsstruktur; Aufsatzsammlung; Europa; Islamieten; Sociale netwerken; Minderheden; Acculturation; Conflit culturel; Diaspora; Islam; Mass-média.; Minorité religieuse; Musulman; Relations interreligieuses; Transnationalisme; Europe